GENERASI INDIGO - Madyawati, Lilis (Universitas Muhammadiyah Magelang, 2011)
Indigo child fenomenon typical minded suspected due to a mistake in the performance of the brain (brain worksystems) are disrupted. They are more than normal children interns of empathy and creativity and unique behavioral characteristics. Because it has a sixth sense, they are considered to have ability to describe past and future. In order for the development of his soul is not disturbed, it?s better indigo children are treated fairly.